Perceived social integration, motives, internet use, and willingness to express opinion: antecedents and effects of time online - Khan, Fazal Rahim (IIUM Press, 2009)
This study tests antecedents and effects of time spent online in a random sample of senior level undergraduate students at a public university in Malaysia. The path analysis found that a perceived social integration predicted time spent online and opinion expression in public on one of the two issues in the study. Surveillance-social connectivity motives both mediated and moderated the social integration and time on online linkage. As an endogenous predictor, time spent on online predicted opinion expression on both the issues. Implications of these findings are discussed from the standpoint of the spiral of silence theory, and the Internet use literature.